Analysis of The Influence of Digital Perceived Value, Digital Perceived Quality and Brand Image on Intention to Return Visits of Tourists in Indonesia - Maksimilianus Gai, Ardiyanto; Majid, Jamaluddin; Risdwiyanto, Andriya; Alvionita Paru, Maria; Effendy, Femmy (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to examine how visitor satisfaction, which affects their intention to return to tourist destinations, is influenced by perceived quality, destination image, and perceived value. Researchers employed a conclusive research design in this study. The judgmental sampling approach is a non-probability sampling methodology that was employed by the researcher. 100 people made up the study's sample. The major data used in this study came from the responses to questionnaires that were distributed. In this study, structural equation modeling is employed. It is clear from the analysis's findings that travelers' perceptions of a destination's quality, value, contentment, and likelihood to return are significantly influenced by its image. Travelers' perceived quality, perceived value, level of satisfaction, and inclination to return are all positively correlated with the destination's image. Perceived quality also significantly positively affects satisfaction, perceived value, and inclination to return. Perceived value also significantly positively affects satisfaction and the desire to return. The inclination to return is significantly positively impacted by satisfaction as well. These findings suggest that in order to boost visitor happiness and loyalty toward tourism attractions, destination management must focus on and enhance destination image, service quality, and perceived value.